How to Address the Policy and Ethical Issues Emerging with New Technology. The Case of Synthetic Biology in a Small Country. - Mali, Franc (NanoEthics, 2018)
Synthetic biology (SB) is rather a new field of science and technology. Societal, regulatory, legal, ethical, safety and security aspects of this field have already been analysed in much detail and discussed very widely in recent years. There is, however, a dearth of empirical studies on the points of view of relevant stakeholders in countries where SB is still in the process of emergence. Slovenia is one of them, and accordingly, the article analyses the situation of SB in this small country, focusing on the points of view of various stakeholder groups concerning three aspects of SB: the policy framework, the ethical-legal discourse and the issues of biosafety and biosecurity. It is argued that Slovenia has missed many opportunities to foster the domestic development of the field; in particular, considering that at an early stage, young Slovenian researchers participated very successfully in the International Genetically Engineered Machine (iGEM) competition.